Occurrence of blossom-end rot in tomatoes (Lycopersicon esculentum Mill.) under effect of growth regulators - Castro, Paulo R. C.; Malavolta, Eurípedes (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
It was observed that gibberellic acid 100 ppm promotes high incidence of blossom-end rot when a high level of ammonium sulphate was used. Under the same conditions, treatments with succinic acid -2,2-dimcthylhydrazide 4,000 ppm, (2-chloroethyl) trimethylammonium chloride 2,000 ppm and indole-3-acetic acid 100 ppm, caused, low incidence of blossom-end rot. It was proposed a mechanism of blossom-end rot incidence in tomatoes.